Meretas Polarisasi Pendidikan Kristiani: Sebuah Pengantar tentang Arah Pendidikan Kristiani di Gereja, Akademia, dan Ruang Publik - Binsen S. Sidjabat (Indonesian Journal of Theology, 2019)
This paper presents an introduction for understanding Christian education holistically. The discussion of Christian education to follow covers not only Christian Religious Education (Pendidikan Agama Kristen, PAK) in the context of schools and Congregation Membership Development (Pembinaan Warga Gereja, PWG), but also higher education contexts where instruction is oriented fundamentally according to Christian faith. Emphasized, as well, is the inseparable connection between Christian education for the formation and development of faith, spirituality, and character, and the formation and development of knowledge (academia) and life skills.